A Vavraia-like microsporidium as the cause of deadly infection in threatened and endangered Eurycea salamanders in the United States - Xue Yu; Rachel L. Hoyle; Fengguang Guo; Cameron M. Ratliff; Valentin Cantu; Justin Crow; Lixin Xiang; J. Jill Heatley; Guan Zhu (Parasites & Vectors, 2019)
Abstract Background Eurycea sosorum (Barton Springs salamander) and Eurycea nana (San Macros salamander) are listed as endangered and threatened species, respectively, by the U.S. Fish and Wildlife Service (USFWS) with habitats restricted to small regions near Austin, Texas, USA. The conservation efforts with the Eurycea salamanders at the captive breeding program in San Marcos Aquatic Resources Center (SMARC), a USFWS facility, have seen an unexpected and increased mortality rate over the past few years. The clinical signs of sick or dead salamanders included erythema, tail loss, asymmetric gills or brachial loss, rhabdomyolysis, kyphosis, and behavior changes, suggesting that an infectious disease might be the culprit. This study aimed to identify the cause of the infection, determine the taxonomic position of the pathogen, and investigate the potential reservoirs of the pathogen in the environment. Results Histopathological examination indicated microsporidian infection (microsporidiosis) in the sick and dead Eurycea salamanders that was later confirmed by PCR detection. We also determined the near full-length small subunit ribosomal RNA (SSU rRNA) gene from the microsporidian pathogen, which allowed us to determine its phylogenetic position, and to design primers for specific and sensitive detection of the pathogen. Phylogenetic analysis indicated that this pathogen was closely related to the insect parasites Vavraia spp. and the human opportunistic pathogen, Trachipleistophora hominis. This Vavraia-like microsporidium was present in dead salamanders at SMARC archived between 2011 and 2015 (positive rates ranging between 52.0–88.9% by PCR detection), as well as in some aquatic invertebrates at the facility (e.g. snails and small crustaceans). Conclusions A Vavraia-like microsporidian was at least one of the major pathogens, if not solely, responsible for the sickness and mortality in the SMARC salamanders, and the pathogen had been present in the center for years. Environmental invertebrates likely served as a source and reservoir of the microsporidian pathogen. These observations provide new knowledge and a foundation for future conservation efforts for Eurycea salamanders including molecular surveys, monitoring of the pathogen, and discovery of effective treatments.